Performance Evaluation of Large-Size Commercial Banks in India - Devanadhen, K. (Indian Journal of Finance, 2013)
Financial soundness of the banking sector is the backbone of a country’s economy. This paper studies the performance of 14 public sector and 3 private sector banks under the CAMELS model for the period from April 1, 2000 to March 31, 2011. In the liberalized environment, the private sector banks give a very tough competition to the public sector banks in terms of Earning Capacity, Management Efficiency and Asset Quality. After evaluation as per the CAMELS Model, it was found that the Andhra Bank secured the first place followed by Corporation Bank and HDFC Bank. Axis Bank and ICICI Bank were ranked 6th and 14th respectively. Central Bank of India stood last in the overall performance ; and SBI (largest public sector bank) exhibited better performance than ICICI Bank ( largest private sector bank).